Effective design of e-learning application incorporating multiple intelligences - Krishnasamy, Kemalatha; Lee, Sai; Palaniappan, Sellappan (2003)
Electronic learning (e-learning) is currently a common concept, and this is due to an attempt by many educational sectors to develop structures and systems that are more adaptable and responsive to changes. The real effectiveness of e-learning applications lies in the recognition by the educator and the learner that all people have learning strengths and weaknesses. Within the field of computer science in general and education in particular, there is not much emphasis on the importance of developing an effective electronic learning application that caters for all types of people. Therefore, there is a need to develop an electronic learning application that is not complicated and difficult to use but at the same time considering the various types of learners. This study reviews design strategies for an e-learning application in smart schools and discusses the two main perspectives on the education sector, that is, the focus on generative teaching or learning without incorporating Multiple Intelligences (MI) and the focus on teaching/learning based on Multiple Intelligences where various approaches of learners are considered. Students from selected smart schools in Malaysia participated in Multiple Intelligence assessment based on Dr. Howard Gardner's theory of Multiple Intelligences for determining basic intelligence. Students were also surveyed on their attitude towards electronic learning. Finally, correlation coefficients were computed to match online design of activities with their competencies and characteristics according to their intelligences. The findings of the survey indicate that students with visual/spatial and interpersonal intelligences use and benefit more from online learning and prefer them to traditional instructional strategies techniques when compared with students whose intelligences are verbal/linguistic, logical/mathematical, bodily kinesthetic and intrapersonal. Furthermore, the findings show that some online activities appear to be generic across all applications. The purpose of this study is to determine the success factors in using the Internet for the propagating of learning in Malaysian schools. A secondary purpose is to evaluate the appropriateness and effectiveness of using the online materials and activities prepared in accordance with Multiple Intelligences to enhance the process of teaching and learning at the secondary school level. These issues will form the basis of developing a set of criteria for the integration of the teaching/learning vision, measurement of goals, internal/external data collection, inventiveness and proactive implementation. Educational providers should not plan activities based solely upon popularity. Learning activities are likely to be most effective when the perceived preferred learning mode is combined with a variety of other activities associated with the learning style of an individual based on Multiple Intelligences. The incorporation of Multiple Intelligences in electronic learning strategies provides a degree of flexibility in the way students can undertake their learning and provide a collaborative and interactive environment.